Análise do espaçamento entrelinhas em semeadura de fileira dupla em genótipos de soja no município de Alegrete - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The objective of this work was to perform the conventional row spacing of 0.45m and paired row arrangement, spaced 0.35 meters apart, in order to identify which row spacing presented the best productivity, as well as the influence of the arrangement. It was used two cultivars with different ripening cycle, evaluating their performance under edaphoclimatic conditions in the city of Alegrete, in 2018/2019. Sowing was performed in the second half of November 2018, where it presented three row spacings (0.35 / 0.40, 0.35 / 0.50 and 0.35 / 0.60) meters using the sowing density. 250 thousand plants per hectare. First knot height, total plant height, grain per pod, number of fertile nodes, total number of grains, number of pods per plant, total number of nodes, weight of 1000 grains and yield were identified. Enabling the grower to identify whether it is feasible to use double row seeding and the influence of spacing, at the end of the experiment it was found that the variation of spacing between paired rows and between conventional spacing changed some plant characteristics, however there was no difference. productivity with the 5% probability Tukey test.
Keywords: Engenharia agrícola; Semeadura; Espaçamento; Soja; Agricultural engineering; Seeding; Spacing; Soy; CNPQ::CIENCIAS AGRARIAS